Analisis Pendapatan dan Kelayakan Usaha Pengumpulan Tiram di Kawasan Pesisir Kota Lhokseumawe - Martina; eka maida; Dewi Kumala Sari (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2026)
Oyster gathering is one of the economic activities carried out by coastal communities to support household income. This study aims to analyze the income level and business feasibility of oyster gathering in the coastal area of Lhokseumawe City. The research employed a quantitative descriptive approach using survey methods through field observations and interviews with respondents. The population consisted of 45 oyster gatherers, all of whom were selected as respondents using a census sampling technique. Data analysis included cost analysis, revenue analysis, income analysis, and business feasibility analysis using the Revenue Cost Ratio (R/C Ratio). The results show that the average total cost of oyster gathering is IDR 1,782,875 per month, while the average revenue reaches IDR 5,000,000 per month, resulting in a net income of IDR 3,217,125 per month. The R/C Ratio value of 2.80 indicates that the oyster gathering business is economically feasible and profitable. Therefore, oyster gathering has the potential to serve as an alternative livelihood for coastal communities and contributes to improving household income.